(untitled) (Journal of Finance, Business and Management Studies, 2025)
The study aims to analyze the impact of cultural preservation on economic prosperity of Sambalpur. For the study we collect data from 30 select shops of Sambalpur city through a questionnaire. We measure cultural preservation through various indicators like food, garments, and festivals. Economic prosperity measured by total sales. The study uses Regression and paired T-test to analyze the impact of Cultural preservation on Economic prosperity. The study finds that cultural preservation has a significance impact on Economic prosperity. The results of the study will be helpful for the policy makers to take important decisions.